Influence of vitamin D on cell cycle, apoptosis, and some apoptosis related molecules in systemic lupus erythematosus - Tabasi, Nafise (Iran J Basic Med Sci, 2015)
OBJECTIVE(S): Genetic and environmental factors are involved in the pathogenesis of systemic lupus erythematosus (SLE). Autoreactive lymphocytes are cleared through apoptosis and any disturbance in the apoptosis or clearance of apoptotic cells may disturb tolerance and lead to autoimmunity. Vitamin D has anti-proliferative effects and controls cell cycle progression. In this study we investigated the effects of vitamin D on cell cycle and apoptosis induction in lupus patients. MATERIALS AND METHODS: Isolated peripheral blood mononuclear cells (PBMCs) from 25 SLE patients were cultured in the presence of 50 nM of 1,25(OH)2D3; then one part of the cells were stained with FITC labeled Annexin V and PI and were analyzed for apoptosis determination. For gene expression assessment of FasL, Bcl-2 and Bax, RNA was extracted from one another part of the cells, cDNA was synthesized and gene expression analysis was performed using Real time PCR. An additional part of the cells were treated with PI and the cell cycle was analyzed using flowcytometer. RESULTS: The mean number of early apoptotic cells in vitamin D treated cells decreased significantly (18.48±7.9%) compared to untreated cells (22.02±9.4%) (P=0.008). Cell cycle analysis showed a significant increase in G1 phase in vitamin D treated cells (67.33±5.2%) compared to non treated ones (60.77±5.7%) (P =0.02). Vitamin D up-regulated the expression levels of Bcl-2 by (18.87 fold increase), and down-regulated expression of Bax (23%) and FasL (25%). CONCLUSION: Vitamin D has regulatory effects on cell cycle progression, apoptosis and apoptosis related molecules in lupus patients.